Improving Social Studies learning activity and outcomes through multimedia-based learning - Winarsi, Winarsi; Azizah, Primanisa Inayati; Rosardi, Raras Gistha; Setya Dhewantoro, Happri Novriza (JIPSINDO, 2025)
This research was motivated by the low learning activity and low learning outcomes of social studies of class VII/B students in the second semester at SMP Negeri 2 Dusun Selatan. Indicators of low learning activity include a lack of enthusiasm for learning and a tendency to be apathetic in participating in learning. This can be seen from students' responses to teacher questions, their activeness in expressing opinions or ideas, and low student participation in learning. Meanwhile, indicators of low learning outcomes are seen from classical completeness, which is still below 75% with the KKM value of Social Studies for Class VII in the second semester of the 2024/2025 Academic Year at SMP Negeri 2 Dusun Selatan being 70. To overcome this problem, a Classroom Action Research was conducted that focused on increasing activity and improving learning outcomes through the use of multimedia-based learning media. This Classroom Action Research (CAR) used the Kemmis and McTaggart model, which was implemented in 2 (two) cycles on 31 students. Data was collected through learning activity observations, learning outcome tests, and student response questionnaires. The results showed a significant increase in learning activity, learning outcomes, and classical mastery. Learning activity increased by 17.4%, from 68.9% pre-cycle to 75.4% in Cycle 1 and 86.3% in Cycle 2. Student learning outcomes increased by 13.9%, from 72.6% in the pre-cycle to 80.3% in Cycle 1 and 87.7% in Cycle 2. Classical mastery percentage increased by 29%, from 65% in the pre-cycle to 83% in Cycle 1 and 94% in Cycle 2. It was concluded that the use of multimedia-based learning media can improve the social studies learning activity and learning outcomes of grade VII/B students in the 2024/2025 academic year at SMP Negeri 2 Dusun Selatan.